Who benefits from the rapidly increasing voluntary sustainability standards? Evidence from fairtrade and organic certified coffee in Ethiopia - Minten, Bart; Dereje, Mekdim; Engeda, Ermias; Tamru, Seneshaw (International Food Policy Research Institute, 2014)
Voluntary Sustainability Standards (VSS) are rapidly increasing in global value chains. While consumers, mostly in developed countries, are willing to pay significant premiums for such standards, it is not well understood how effectively these incentives are transmitted to producing countries. We study VSS in Ethiopia’s coffee sector, the country’s most important export commodity, using a unique census of transaction data at the export level and large-scale data at the production level. We find that transmission of the export quality premiums to coffee pro-ducers is limited, with only one-third of this premium being passed on. Moreover, as quality premiums are small and average production levels in these settings are low, these premiums would only lead to an increased income for coffee farmers of 20 USD per year even with a perfect transmission scenario, and therefore would have little effect on the welfare of the average coffee farmer.